741. Impact of Adenovirus Co-detections on Illness Severity. (26th November 2018) - Probst, Varvara; Piya, Bhinnata; Stewart, Laura; Gerber, Susan; Rha, Brian; Yu, Joana; Das, Suman; Campbell, Angela P; Williams, John V; Halasa, Natasha B
Abstract: Background: Human adenovirus (AdV) is a common pathogen among children with acute respiratory illnesses (ARI) and is often associated with co-detection with other respiratory viral pathogens. We sought to compare demographic and clinical characteristics in children with ARI who had single-AdV vs. AdV-co-detection with other viruses. Methods: Children <18 years with fever and/or ARI were enrolled in Vanderbilt Children's Hospital inpatient setting from 2015 to 2018 and emergency department from 2016 to 2018. Interviews were conducted using standardized case report forms. Nose and throat swab specimens were collected and tested by RT-qPCR for common respiratory pathogens (AdV, RSV, HRV, hMPV, PIV1–4 and Influenza). Results: Of 2, 740 ARI cases, 174 were positive for AdV [88 (51%) single detection], with 53% male, 47% White, 36% Black, 30% Hispanic and median age of 17.2 months. Co-detected pathogens in AdV-positive specimens were RSV(15%), HRV(14%), influenza(5%), PIV1(1%), PIV2(0.6%), PIV3(1.7%), and PIV4(0.6%), hMPV(3%), >1 co-pathogens(9%). Subjects with single-AdV detection were more likely to have an underlying medical condition (42% vs. 24%, P < 0.05). Table 1 compares clinical presentation and severity of single-AdV and AdV-co-detection cases. Conclusion: Patients with single-AdV detection were less likely to present with ARI symptoms and require oxygen, but were more likely to have underlying medical conditions compared with AdV-co-detection. Further studies to type AdV isolates will help elucidate the role of specific adenovirus types associated with co-detections and illness severity and inform epidemiological information for future vaccine initiatives. Disclosures: J. V. Williams, Quidel: Board Member, Consulting fee. GlaxoSmithKline: Consultant, Consulting fee. N. B. Halasa, sanofi pasteur: Investigator, Research support. GSK: Consultant, Consulting fee. Moderna: Consultant, Consulting fee.